1989
DOI: 10.1103/physrevlett.63.1292
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-impact fusion

Abstract: Deuteron-deuteron fusion, detected via the 3-MeV protons produced, is shown to occur when singly charged clusters of 25 to 1300 D2O molecules, accelerated to 200 to 325 keV, impinge on TiD targets. The energy and cluster-size dependence of the fusion rate are discussed. The fusion events are shown to originate from the cluster-ion impacts rather than from D + or D2O 4 " ions in the beam. The observed rates may be correlated with the compressions and high energy densities created in collision spikes by cluster-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(53 citation statements)
references
References 8 publications
1
51
0
1
Order By: Relevance
“…In their model the fusion rate is proportional to I ~dEe -E/Eo e -A/ ./E 0 where they assume E 0 = 500 ev, and A= 31.28 kevl/ 2 [1]. However, Echenique et al are careful to note the sensitivity of the fusion rate to the value of Ea.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In their model the fusion rate is proportional to I ~dEe -E/Eo e -A/ ./E 0 where they assume E 0 = 500 ev, and A= 31.28 kevl/ 2 [1]. However, Echenique et al are careful to note the sensitivity of the fusion rate to the value of Ea.…”
Section: Introductionmentioning
confidence: 99%
“…Since such a high fusion rate would require an unrealistically high fusion cross section for an uncompressed system, they have suggested that the incoming clusters create shock waves that result in significant compression of the cluster and target material [ 1] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, it is established that the cluster energy-loss is different from the sum of energy losses of its separated components. An increased energy transfer due a cluster may even be used in inertial nuclear fusion processes [3,4].…”
Section: Introductionmentioning
confidence: 99%